The Impact of Debt Policy, Dividend Policy, and Investment Decisions on Value Creation (Study of Coal Mining Companies listed on the IDX for the 2018-2022 Period) - Maulana, Yasir; Marliani, Ana; Komarudin, Munir Nur (Asosiasi Ahli Administrasi Indonesia, 2024)
The aim of this reseacrh is to identify and analyze the combined impact of debt policy, dividend policy, and investment decisions on value creation, the influence of debt policy on value development, and the influence of dividend policy on value creation. The study also aims to investigate the influence of investment choices on value generation. We conducted this study at coal mining businesses listed on the IDX between 2018 and 2022. This study had a sample size of seven coal mining companies. The preliminary findings indicate that debt management has a significant and favorable influence on value generation. Similarly, the policy regarding dividends also has a positive and significant impact on value creation. Furthermore, investment decisions have a positive and significant impact on value creation for coal mining firms listed on the IDX between 2018 and 2022.